The Effect of Mashing Methods on the Production of Nonalcoholic Sorghum Malt Beverage - G. M. Elgorashi, Ahmed; A. Elkhalifa, Elamin; E. Sulieman, , Abdel moneim; A. Mudawi, Hassan (Gezira Journal of Engineering and Applied Sciences; مجلد 11 عدد 2 (2016), 2016)
Although sorghum ( Sorghum bicolor ) has been used traditionally to produce foods, malt and alcoholic beverages in Sudan, its structure and nutritional function have not been enough studied. Sorghum can be malted and processed into malted foods and beverages. The objective of this study was to study the effect of mashing methods on malt quality and wort composition to produce non-alcoholic sorghum malt beverage.  Malting was carried out at 30°C for 5 days under non-aerated condition. Mashing methods included decantation at 80°C (wort A) and at 100°C (wort B). Wort composition in terms of α –amino nitrogen, total soluble nitrogen, reducing sugars, pH, colour, original gravity and viscosity were determined. The results of wort A were 114 mg/l, 43%, 39.42 mg/ml, 6.59, 9 EBC, 1.026 and 0.846 cP, respectively. Whereas the results of wort B were 125 mg/l, 53%, 41.67 mg/ml, 6.68, 11 EBC, 1.025 and 0.864 cP, respectively. Decantation mashing at 100°C produced much better results in terms of malt and wort properties than that at 80°C where boiling the mash at 100°C adequately gelatinized residual sorghum malt starch, since sorghum starch has a gelatinization temperature of 80°C.